PENGARUH MIKROORGANISME LOKAL BUAH-BUAHAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) - Raras, Noorvita; hadid, Abdul; latarang, Burhanuddin (AGROTEKBIS, 2018)
This study aims to know the effect of local fruit microorganisms on growth and lettuce yield. The method used in this research was by using Randomized Block Design with treatment of local microorganisms of fruits on lettuce crop consisting of seven levels and repeated 3 times to get 21 units of experiment. Seven treatment dosage levels are: K0 = Without microorganism, K1 = 1L / 5L Water (200 ml), K2 = 1L / 10L Water (66 ml), K3 = 1L / 15L Water (66 ml), K4 = 1L / 20L Water (50 ml), K5 = 1L / 25L Water (40 ml) and K6 = 1L / 30L Water (33 ml). Parameters observed were Plant Height, Total Leaf, Total Fresh Weight and Dry Plant Weight. From the results of research on the influence of local microorganisms of fruits on the growth and yield of lettuce plants, the concentration of liquid fertilizer of local fruits microorganisms provide a real effect on the growth and yield of lettuce plants. The treatment of liquid fertilizer local fruits microorganisms with a concentration of 10% yielded the highest plant height, highest number of leaves, wet weight and highest dry weight.Â Key Words: Lettuce, Local Microorganisms Fruits,